THERMAL CONDUCTIVITY OF LIMESTONE - Rozali, Attia (Universiti Teknologi PETRONAS, 2010)
This ~eport discusses the research that has been done on order to understand Thermal Conductivity of Limestone and starts to make a relationship on any occurrence in the reservoir. Thermal conductivity is a thermal property that describes heat flow from one location to .jl !IO~jler. Thermal Conductivity is important in analyzing the thermal maturation in'org:anic matter in hydrocarbon research. The'l"al ~onductivity is one 9f the important parameters that describe heat flow. The objectivq of ~is research is to estimate thermal conductivity of limestone and also to \ see the other p~{lmyters that affect thermal conductivity by conducting experiment and measures the ran~e of mineralogical ~uch as XRD, XRF & FESEM.